2021
DOI: 10.1002/cam4.3718
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of PD‐1/PD‐L1 inhibitors combined with radiotherapy in patients with non‐small‐cell lung cancer: a systematic review and meta‐analysis

Abstract: Background A combination of programmed cell death protein‐1 (PD‐1)/programmed cell death ligand‐1 (PD‐L1) inhibitors and radiotherapy (RT) is increasingly being used to treat non‐small‐cell lung cancer (NSCLC). However, the safety and efficacy of this approach remains controversial. We performed a systematic review and meta‐analysis to summarize the related research. Methods We searched the China Biology Medicine, EMBASE, Cochrane Library, and PubMed databases for all the relevant studies. The Stata software, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 65 publications
0
41
1
Order By: Relevance
“…The results of multivariable Cox proportional hazard regression analysis showed that the timing of TACE and drug combination therapy was an independent risk factor for OS and PFS. Previous studies have also shown that sequential use of immune checkpoint inhibitors after radiotherapy improves patient survival compared to concurrent use in other tumors [ 27 , 28 ]. Late combination had longer survival and progression-free survival compared to early combination, which may be due to the following reasons: (1) The tumor microenvironment in advanced HCC is in an immunosuppressed state, especially in patients with co-infection with chronic hepatitis B. T cells are dysfunctional.…”
Section: Discussionmentioning
confidence: 99%
“…The results of multivariable Cox proportional hazard regression analysis showed that the timing of TACE and drug combination therapy was an independent risk factor for OS and PFS. Previous studies have also shown that sequential use of immune checkpoint inhibitors after radiotherapy improves patient survival compared to concurrent use in other tumors [ 27 , 28 ]. Late combination had longer survival and progression-free survival compared to early combination, which may be due to the following reasons: (1) The tumor microenvironment in advanced HCC is in an immunosuppressed state, especially in patients with co-infection with chronic hepatitis B. T cells are dysfunctional.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy can be applied in all stages of disease. Our previous study showed that inspiring results were obtained with radiotherapy combined with immunotherapy [ 3 ]. However, radioresistance is acknowledged as a factor related to failure of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several clinical studies showed improved clinical outcomes when radiation is added to ICBs. In a meta-analysis including 20 clinical trials and 2,027 NSCLC patients, the combination of anti-PD1/PD-L1 inhibitors with radiotherapy was associated with significantly improved objective response rate (odds ratio [OR] 2.76, 95% CI 1.06–7.19, p = 0.038) and OS (2-year survival HR 1.77, 95% CI 1.35–2.33, p = 0.000) [ 85 ]. Currently, durvalumab has been approved as a maintenance therapy after platinum-based chemoradiation therapy for stage III NSCLC patients based on a Phase III PACIFIC trial [ 86 , 87 ].…”
Section: Combination Of Radiation Therapy With Immunotherapymentioning
confidence: 99%